Quality assurance of quantitative cardiac T1-mapping in multicenter clinical trials – A T1 phantom program from the hypertrophic cardiomyopathy registry (HCMR) study. (1st May 2021) - Zhang, Qiang; Werys, Konrad; Popescu, Iulia A.; Biasiolli, Luca; Ntusi, Ntobeko A.B.; Desai, Milind; Zimmerman, Stefan L.; Shah, Dipan J.; Autry, Kyle; Kim, Bette; Kim, Han W.; Jenista, Elizabeth R.; et al.
Abstract: Background: Quantitative cardiovascular magnetic resonance T1-mapping is increasingly used for myocardial tissue characterization. However, the lack of standardization limits direct comparability between centers and wider roll-out for clinical use or trials. Purpose: To develop a quality assurance (QA) program assuring standardized T1 measurements for clinical use. Methods: MR phantoms manufactured in 2013 were distributed, including ShMOLLI T1-mapping and reference T1 and T2 protocols. We first studied the T1 and T2 dependency on temperature and phantom aging using phantom datasets from a single site over 4 years. Based on this, we developed a multiparametric QA model, which was then applied to 78 scans from 28 other multi-national sites. Results: T1 temperature sensitivity followed a second-order polynomial to baseline T1 values (R 2  > 0.996). Some phantoms showed aging effects, where T1 drifted up to 49% over 40 months. The correlation model based on reference T1 and T2, developed on 1004 dedicated phantom scans, predicted ShMOLLI-T1 with high consistency (coefficient of variation 1.54%), and was robust to temperature variations and phantom aging. Using the 95% confidence interval of the correlation model residuals as the tolerance range, we analyzed 390 ShMOLLI T1-maps and confirmed accurate sequence deployment in 90%(70/78) of QA scans across 28 multiple centers, and categorized the rest with specific remedial actions. Conclusions: The proposed phantom QA for T1-mapping can assure correct method implementation and protocol adherence, and is robust to temperature variation and phantom aging. This QA program circumvents the need of frequent phantom replacements, and can be readily deployed in multicenter trials. Highlights: CMR T1 correlated with reference T1 and T2; this derives the QA model for T1-map. The proposed QA model is robust to temperature variations and phantom aging. This QA method requires no frequent phantom replacements. The T1-map QA program can be readily deployed in multicenter trials.